Personalized therapy algorithms for type 2 diabetes: a phenotype-based approach - Ceriello A; Gallo M; Candido R; De Micheli A; Esposito K; Gentile S; Medea G (Dove Medical Press, 2014)
Antonio Ceriello,1,2 Marco Gallo,3 Riccardo Candido,4 Alberto De Micheli,5 Katherine Esposito,6 Sandro Gentile,6 Gerardo Medea71Department of Endocrinology, Hospital Clinic de Barcelona, Institut d’Investigacions Biomèdiques August Pi iSunyer, 2Centro de Investigacion Biomèdica en Red de Diabetes y Enfermedades Metabolicas Asociadas, Barcelona, Spain; 3Oncological Endocrinology, AOU Città della Salute e della Scienza-Molinette, Turin, 4Diabetes Center, ASS 1 Triestina, Trieste, 5Ligurian Health Agency, Genoa, 6Department of Clinical and Experimental Medicine, Second University of Naples, Naples, 7Italian College of General Practitioners, Florence, ItalyAbstract: Type 2 diabetes is a progressive disease with a complex and multifactorial pathophysiology. Patients with type 2 diabetes show a variety of clinical features, including different "phenotypes" of hyperglycemia (eg, fasting/preprandial or postprandial). Thus, the best treatment choice is sometimes difficult to make, and treatment initiation or optimization is postponed. This situation may explain why, despite the existing complex therapeutic armamentarium and guidelines for the treatment of type 2 diabetes, a significant proportion of patients do not have good metabolic control and at risk of developing the late complications of diabetes. The Italian Association of Medical Diabetologists has developed an innovative personalized algorithm for the treatment of type 2 diabetes, which is available online. According to the main features shown by the patient, six algorithms are proposed, according to glycated hemoglobin (HbA1c, ≥9% or ≤9%), body mass index (≤30 kg/m2 or ≥30 kg/m2), occupational risk potentially related to hypoglycemia, chronic renal failure, and frail elderly status. Through self-monitoring of blood glucose, patients are phenotyped according to the occurrence of fasting/preprandial or postprandial hyperglycemia. In each of these six algorithms, the gradual choice of treatment is related to the identified phenotype. With one exception, these algorithms contain a stepwise approach for patients with type 2 diabetes who are metformin-intolerant. The glycemic targets (HbA1c, fasting/preprandial and postprandial glycemia) are also personalized. This accessible and easy to use algorithm may help physicians to choose a personalized treatment plan for each patient and to optimize it in a timely manner, thereby lessening clinical inertia.Keywords: type 2 diabetes, treatment guidelines, personalized treatment, Italian Association of Medical Diabetologists, Italian algorithm